New “Ex Vivo” Radioisotopic Method of Quantitation of Platelet Deposition – Studies in Four Animal Species - Badimon, L; Fuster, V; Chesebro, J H; Dewanjee, M K (Thrombosis and Haemostasis, 1983)
We have developed a sensitive and quantitative method of “ex vivo” evaluation of platelet deposition on collagen strips, from rabbit Achilles tendon, superfused by flowing blood and applied it to four animal species, cat, rabbit, dog and pig. Autologous platelets were labeled with indium-111-tropolone, injected to the animal 24 hr before the superfusion and the number of deposited platelets was quantitated from the tendon gamma-radiation and the blood platelet count.We detected some platelet consumption with superfusion time when blood was reinfused entering the contralateral jugular vein after collagen contact but not if blood was discarded after the contact. Therefore, in order to have a more physiological animal model we decided to discard blood after superfusion of the tendon.In all species except for the cat there was a linear relationship between increase of platelet on the tendon and time of exposure to blood superfusion. The highest number of platelets deposited on the collagen was found in cats, the lowest in dogs.Ultrastructural analysis showed the platelets were deposited as aggregates after only 5 min of superfusion.
Keywords: Platelet deposition; Platelet labeling; Platelet activation